Pengaruh User Generated Content dan Bundling Product Terhadap Keputusan Pembelian Konsumen Pada Produk Glad2Glow di Kota Medan: Pengabdian - Yeni Haryanti Purba; Nana Dyki Dirbawanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid development of digital technology today has driven major changes in the beauty industry, along with the increasing public awareness of skincare. In attracting consumers, effective marketing strategies are essential, one of which is through the utilization of user-generated content and product bundling. This study aims to analyze the influence of User-Generated Content and Product Bundling on Consumer Purchase Decisions for Glad2Glow products in Medan City. The research method employed is quantitative with an associative approach, using a sample of 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that User-Generated Content (t = 5.118 > 1.984) and Product Bundling (t = 6.406 > 1.984) have a positive and significant influence on purchase decisions. Simultaneously, both variables significantly affect purchase decisions with an Adjusted R Square value of 0.600, which means that 60% of the variation in purchase decisions can be explained by these two variables, while the remaining 40% is influenced by other factors outside the study. These findings provide empirical insights into the contribution of user-generated content and product bundling in influencing consumer purchase decisions within the context of beauty products in Medan City.